(untitled) (Proceedings of Faculty of Civil Engineering, 2023)
The research that was conducted as part of scientific and development project UNIRI INOVA "New connector for joining structural elements made of thin-walled steel C-profiles" was presented. The project goal is to provide better knowledge about the behavior of new connection components for joining elements made of thin-walled steel C-profiles.